FREESTYLE SKILLS (CRAWL) IN SWIMMING SPORTS ON STUNNING STOK BINA GUNA STUDENTS - Muhammad Syaleh (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
The problem in this research is how the freestyle skills (crawl) in swimming in the 2019 STOK Bina Guna students aiming to find out the freestyle skills (crawl) in the 2019 STOK Bina Guna students and assist the lecturer in implementing the learning process of swimming basic techniques . The method used in this research is descriptive method and this form of research is survey research. The sample used was 50 students. Based on the results of the study The results of this study found that the average student can do freestyle skills with an excellent category of 6%, 42% good, 28% enough, less 14% and less than 10%. From the results of the study, 2019 STOK Bina Guna students can do freestyle skills correctly and have different categories so that the learning process can be carried out smoothly because all students can do freestyle swimming (crawl) in swimming subjects.